Crossing the Next Frontier: The Role of ICT in Driving the Financialization of Credit. (September 2017) - Drummer, Daniel; Feuerriegel, Stefan; Neumann, Dirk
Financialization describes a phenomenon whereby financial markets assume an increasingly dominant role within the economy. This paper seeks to dissect the role of information and communications technology (ICT) in financialization by following a cross-disciplinary approach across finance, economics and information systems. Accordingly, we develop a general framework describing the relationship between ICT and financialization. This framework allows us to investigate the recent rise of online marketplaces for credit. Consequently, ICT is not only facilitating, but fundamentally driving a disintermediation of banks through advances in computing, communication and information technology. We also provide supporting evidence from interviews with almost 40 senior experts and C-level executives. Interestingly, only rather recent innovations have enabled the popularity of marketplace lending, such as cloud computing, big data, scalable IT infrastructures and comprehensive ecosystems of programming interfaces. In contrast, we observe a slow integration of advanced analytics in the field of risk management. Based on our analysis, the paper also discusses cross-country implications for marketplace lending, financialization and regulation.